Causal effects of the gut microbiome on COVID-19 susceptibility and severity: a two-sample Mendelian randomization study - Zhong, Meng-Mei; Xie, Jia-Hao; Feng, Yao; Zhang, Shao-Hui; Xia, Jiang-Nan; Tan, Li; Chen, Ning-Xin; Su, Xiao-Lin; Zhang, Qian; Feng, Yun-Zhi; Guo, Yue (Frontiers in Immunology, 2023)
The coronavirus disease 2019 (COVID-19) caused a global pandemic, with potential severity. Most clinical studies have shown an association between SARS-CoV-2 infection and changes in the gut microbiome, however, whether the gut microbiome has a causal relationship with COVID-19 is uncertain. We aimed to investigate whether genetically predicted gut microbiome is associated with susceptibility and severity of COVID-19 risk. Mendelian randomization (MR) analysis of two sets with different significance thresholds were carried out to infer the causal relationship between the gut microbiome and COVID-19. SNPs associated with the composition of the gut microbiome (n = 5,717,754) and with COVID-19 susceptibility (n = 14,328,058), COVID-19 severity (n = 11,707,239), and COVID-19 hospitalization (n = 12,018,444) from publicly available genome-wide association studies (GWAS). The random-effects inverse variance weighted (IVW) method was used to determine causality. Three more MR techniques—MR Egger, weighted median, and weighted mode—and a thorough sensitivity analysis, were also used to confirm the findings. IVW showed that 18 known microbial taxa were causally associated with COVID-19. Among them, 6 microbial taxa were causally associated with COVID-19 susceptibility; 7 microbial taxa were causally associated with COVID-19 severity risk; 5 microbial taxa were causally associated with COVID-19 hospitalization. Sensitivity analyses showed no evidence of pleiotropy or heterogeneity. Then, the predicted 37 species of the gut microbiome deserve further study. In conclusion, this study found that some microbial taxa were protective factors or risk factors for COVID-19, which may provide helpful biomarkers for asymptomatic diagnosis and potential therapeutic targets for COVID-19.